The Movement. Volume 1, Class Warfare - Simone, Gail (DC Comics, 2014)
"Coral City is infected by corruption and crime and its up to the citizens to fight back! The Movement sees a young group of super-heroes rise up and take back the streets of their corrupt city. But when one of their own is captured by the police, its Coral City's finest against the citizens they have negelected to protect. Title collects The Movement #1-6"--